To walk or not to walk - Raja Ariffin, Raja Noriza; Zahari, Rustam Khairi (Association of Malaysian Environment-Behaviour Researchers (AMER), 2018)
Walkability is the basis of a sustainable city. Walking is the socially equitable mode most accessible to the masses. However, the advent of transportation technology has caused the desertion of the pedestrian space. Consequently, the phenomenon created a degradation of the pedestrian environment. The aim of the paper is to examine the characteristics that could promote walking. This paper combines survey questionnaire and walkability audit to gauge perception of the urban walking environment. Findings indicate that the proximity of destinations, good weather condition, safety and well-designed pedestrian facilities can significantly contribute to better perceptions of the walking environment.